SNPs in splicing region and miRNA binding region of Bos taurus TREM-1 gene reveals its association with mastitis - N. S. Pandupuspitasari; F. A. Khan; A. Setiaji; D. A. Lestari; Z. Shujun (Journal of the Indonesian Tropical Animal Agriculture, 2023)
Proper splicing is important for the functioning of a gene, and any interruption in splicing causes several deleterious events. Triggering receptors present on myeloid cells, TREM-1, are implicated in inflammation and act as amplifiers by mediating the release of proinflammatory chemokines and cytokines in response to fungal and bacterial infections. In bovines, mastitis is an inflammatory disease in which mammary gland inflammation is generally caused by bacteria. We found rs109937179 and rs208224995 SNPs in the splicing and miRNA binding region of TREM-1 gene in Chinese Holstein cows. The genotype distribution of the alleles for TREM-1 (rs109937179 and rs208224995) gene polymorphisms was investigated in 364 and 320 Chinese Holstein cows, respectively. We found that the GG genotype of the rs109937179 polymorphism and rs208224995 genotype of CA within the TREM-1 gene were associated with an increased risk of mastitis. Importantly, rs109937179 was found in the splicing region of TREM-1, and rs208224995 has a miRNA binding region for bta-miR- 2329-3p in the 3'UTR, which determines its effective roles in gene expression regulation.